Severe epistaxis due to aberrant vasculature in a patient with STAT‐1 mutation. Issue 3 (7th October 2015) - Chang, Michael T.; Schwam, Zachary G.; Hajek, Michael A.; Paskhover, Boris; Judson, Benjamin L.
Abstract: Background: Signal transducer and activator 1 (STAT‐1) mutations are rare and have been implicated in combined immunodeficiency, enhanced tumorigenesis, and vascular defects. Methods: A 60‐year‐old woman with a novel STAT‐1 mutation and resulting immunodeficiency, squamous cell carcinoma, and vascular disease presented with profuse epistaxis secondary to rupture of an aberrant artery that she developed in part because of this mutation. After unsuccessful posterior packing, embolization was initiated but subsequently aborted because of a bovine origin carotid artery and a history of multiple carotid dissections. Results: After repeat posterior packing, hemostasis was achieved. No additional episodes of epistaxis occurred in the subsequent 13 months. Conclusion: Vascular anomalies can present challenges in epistaxis management. In patients with conditions known to cause vascular anomalies, it is critical to obtain vascular imaging before intervention. © 2015 Wiley Periodicals, Inc. Head Neck 38: E68–E70, 2016